2019
DOI: 10.1021/acs.energyfuels.8b03974
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of Heavy Matrices by Liquid–Liquid Extraction: Part I—How to Separate LMW, MMW, and HMW Compounds in Maltene Fractions of V, Ni, and S Compounds

Abstract: A method using liquid-liquid extractions has been developed for matrix simplification and evaluated by gel permeation chromatography hyphenated with inductively coupled plasma and mass spectrometry (GPC ICP MS). In this method, maltenes were dissolved in n-heptane (HEP), and extractions with methanol (MeOH), acetonitrile (ACN) and dimethylformamide (DMF) were performed. The extraction with ACN is more efficient than that of MeOH for the removal of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…46 A liquid-liquid extraction method for the separation of HMW, MMW and LMW compounds in maltenes (including S-, V-and Ni-containing compounds) was previously developed and had excellent results. 47 Thermo Scientific, Bremen, Germany) operating at a resolution of 4000 was used. The ICP-HR-MS was equipped with an interface based on a microflow total-consumption nebulizer without a drain and was thermoregulated at 60 C to minimize signal suppression and increase the sensitivity by a factor of 3-4.…”
Section: Association Of V and Ni Compounds With Asphaltenes Because mentioning
confidence: 99%
See 1 more Smart Citation
“…46 A liquid-liquid extraction method for the separation of HMW, MMW and LMW compounds in maltenes (including S-, V-and Ni-containing compounds) was previously developed and had excellent results. 47 Thermo Scientific, Bremen, Germany) operating at a resolution of 4000 was used. The ICP-HR-MS was equipped with an interface based on a microflow total-consumption nebulizer without a drain and was thermoregulated at 60 C to minimize signal suppression and increase the sensitivity by a factor of 3-4.…”
Section: Association Of V and Ni Compounds With Asphaltenes Because mentioning
confidence: 99%
“…Complete fractionation method. According to a previous paper 47 that presented a fractionation step for maltenes, Figure 8 shows the mass balance of the complete fractionation protocol for maltene (previous study 47 Table Caption Table 1. Mass percentages of the AS and AI fractions and several physical characteristics of the solvents that were evaluated.…”
Section: Association Of V and Ni Compounds With Asphaltenes Because mentioning
confidence: 99%
“…63 Chauhan et al 64 reported the extraction of vanadium and nickel from diluted oil sand bitumen with hydrochloricacidified, aqueous sodium chloride, and water-diluted ionic liquids, investigated the dissociation equilibria differences and partitioning of vanadium and nickel extraction, and suggested improved extraction of nickel porphyrins with HCl acidification, dilution with aqueous NaCl and dilution with water. Gascon et al 65 . were the first to report the gel permeation chromatography (GPC) separation of vanadium and nickel species found in maltenes.…”
Section: ■ Methods For the Extraction And Purification Of Metalloporphyrinsmentioning
confidence: 98%
“…The authors hypothesize that the final fraction is enriched in disaggregated/free molecules whereas the HMW fraction consists of highly aggregated species, and conclude that liquid-liquid extraction of maltenes with acetonitrile selectively removed low molecular weight vanadium compounds, whereas dimethylformamide extracted low and medium-molecular weight species from the high molecular weight species that remained in the maltene remnant. 65 Notably, the authors documented the separation of three distinct fractions of vanadium and nickel compounds in maltenes based on molecular weight and aggregation tendency determined using GPC. 13 The same authors performed a similar study by directly applying the technique to asphaltene using successive extraction with dimethylformamide, acetone and finally acetonitrile.…”
Section: ■ Methods For the Extraction And Purification Of Metalloporphyrinsmentioning
confidence: 99%
“…This method has already been used to analyse several elements (S, Ni and V, among others) in complex matrices, such as petroleum, [19][20][21][22] atmospheric resid oils 23 and asphaltenes. 24,25 Measuring the molecular weight distribution of known phosphorus-containing species related to their hydrodynamic volume in fatty acid feedstocks can be used as a reference for identifying and understanding those present in lignocellulosic feedstocks like the biocrudes. When performing a chromatographic separation while using GPC columns, which are lled with a porous gel, those analytes with a bigger hydrodynamic volume will elute rst, as their interaction with the gel pores will be lower than those analytes with a lower hydrodynamic volume.…”
Section: Introductionmentioning
confidence: 99%